Maternal Pre-Gravid Obesity Changes Gene Expression Profiles Towards Greater Inflammation and Reduced Insulin Sensitivity in Umbilical Cord - Thakali, Keshari M. (2014)
BACKGROUND: Maternal obesity is associated with unfavorable outcomes, which may be reflected in the as yet undiscovered gene expression profiles of the umbilical cord (UC). METHODS: UCs from 12 lean (pre-gravid BMI < 24.9) and 10 overweight/obese (OW/OB, pre-gravid BMI ≥25) women without gestational diabetes were collected for gene expression analysis using Human Primeview microarrays (Affymetrix). Metabolic parameters were assayed in mother’s plasma and cord blood. RESULTS: Although offspring birth weight and adiposity (at 2-wk) did not differ between groups, expression of 232 transcripts was affected in UC from OW/OB compared to those of lean mothers. GSEA analysis revealed an up-regulation of genes related to metabolism, stimulus and defense response and inhibitory to insulin signaling in the OW/OB group. We confirmed that EGR1, periostin, and FOSB mRNA expression was induced in UCs from OW/OB moms, while endothelin receptor B, KFL10, PEG3 and EGLN3 expression was decreased. Messenger RNA expression of EGR1, FOSB, MEST and SOCS1 were positively correlated (p<0.05) with mother’s first trimester body fat mass (%). CONCLUSIONS: Our data suggest a positive association between maternal obesity and changes in UC gene expression profiles favoring inflammation and insulin resistance, potentially predisposing infants to develop metabolic dysfunction later on in life.